Single-Center Overview of Pediatric Monogenic Autoinflammatory Diseases in the Past Decade: A Summary and Beyond - Wang, Wei; Yu, Zhongxun; Gou, Lijuan; Zhong, Linqing; Li, Ji; Ma, Mingsheng; Wang, Changyan; Zhou, Yu; Ru, Ying; Sun, Zhixing; Wei, Qijiao; Dong, Yanqing; et al. (Frontiers in Immunology, 2020)
Objective: Monogenic autoinflammatory diseases (AIDs) are inborn disorders caused by innate immunity dysregulation and characterized by robust autoinflammation. We aimed to present the phenotypes and genotypes of Chinese pediatric monogenic AID patients. Methods: A total of 288 pediatric patients clinically suspected to have monogenic AIDs at the Department of Pediatrics of Peking Union Medical College Hospital between November 2008 and May 2019 were genotyped by Sanger sequencing, and/or gene panel sequencing and/or whole exome sequencing. Final definite diagnoses were made when the phenotypes and genotypes were mutually verified. Results: Of the 288 patients, 79 (27.4%) were diagnosed with 18 kinds of monogenic AIDs, including 33 patients with inflammasomopathies, 38 patients with non-inflammasome related conditions, and eight patients with type 1 interferonopathies. Main clinical features were skin disorders (76%), musculoskeletal problems (66%), fever (62%), growth retardation (33%), gastrointestinal tract abnormalities (25%), central nervous system abnormalities (15%), eye disorders (16%), ear problems (9%), and cardiopulmonary disorders (8%). The causative genes were ACP5, ADA2, ADAR1, IFIH1, LPIN2, MEFV, MVK, NLRC4, NLRP3, NLRP12, NOD2, PLCG2, PSMB8, PSTPIP1, TMEM173, TNFAIP3, TNFRSF1A, and TREX1. Conclusions: The present study summarized both clinical and genetic characteristics of 18 kinds of monogenic AIDs found in the largest pediatric AID center over the past decade, with fever, skin problems, and musculoskeletal system disorders being the most prevalent clinical features. Many of the mutations were newly discovered. This is by far the first and largest monogenic AID report in Chinese pediatric population and also a catalog of the phenotypic and genotypic features among these patients.